2012
DOI: 10.1186/1756-0500-5-197
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial profile and drug susceptibility pattern of urinary tract infection in pregnant women at University of Gondar Teaching Hospital, Northwest Ethiopia

Abstract: BackgroundUrinary tract infection (UTI) is a common health problem among pregnant women. Proper investigation and prompt treatment are needed to prevent serious life threatening condition and morbidity due to urinary tract infection that can occur in pregnant women. Recent report in Addis Ababa, Ethiopia indicated the prevalence of UTI in pregnant women was 11.6 % and Gram negative bacteria was the predominant isolates and showed multi drug resistance. This study aimed to assess bacterial profile that causes u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

79
184
31
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 185 publications
(301 citation statements)
references
References 19 publications
79
184
31
7
Order By: Relevance
“…This finding is comparable with findings reported in Gondar (91.7%-95%) [15] and Addis Ababa (92.34%). [29] However, this incidence rate is higher than the findings of other studies conducted in Gondar (59.8%) [9] and Addis Ababa (71.7%).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…This finding is comparable with findings reported in Gondar (91.7%-95%) [15] and Addis Ababa (92.34%). [29] However, this incidence rate is higher than the findings of other studies conducted in Gondar (59.8%) [9] and Addis Ababa (71.7%).…”
Section: Discussionsupporting
confidence: 82%
“…[9] According to the Ethiopian standard treatment guideline [27] , trimethoprim-sulphamethoxazole is the first-line drug while, norfloxacin or amoxicillin is an alternative drug for the empiric treatment of uncomplicated UTI. In this study, Gram-negative bacteria showed high resistance to ampicillin, trimethoprimsulphamethoxazole, ceftriaxone, gentamicin and amoxicillin- [9,15,28,29] except the degree of resistance was higher in our cases. Even if the resistance rate and usage of drug is complicated; the cause of resistance for these drugs in this hospital might be deviation from the WHO standard prescription practices [30] which provide an environment or selection of resistant bacteria.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…The involvement of lower and upper urinary tract can lead to asymptomatic bacteriuria and symptomatic bacteriuria, respectively. women and newborn 10,12 if not treated properly.…”
Section: Introductionmentioning
confidence: 99%
“…If urinary tract infection is not controlled, it can badly affect the health of fetus and pregnant women 7,8 . Urinary tract infection during pregnancy may be symptomatic or asymptomatic 9,10 . The involvement of lower and upper urinary tract can lead to asymptomatic bacteriuria and symptomatic bacteriuria, respectively.…”
Section: Introductionmentioning
confidence: 99%